Psychological Defense Mechanisms in Hemingway's Men Without Women - Al-Aghberi, Munir Ahmed (Jurnal Bahasa, Sastra, dan Studi Amerika, 2022)
Applying certain psychological designations to six short stories selected from Hemingway’s Men Without Women, the present paper investigates the variable defense mechanisms that occur in the behavioral manifestations of the fictional characters. The characters’ stressed reactions are examined in accordance with given patterns of defense mechanisms before placing them within the broader framework of autobiographical repressed anxieties. The study concludes that the represented characters project Hemingway's unconscious defenses against three major sources of anxiety: the feminized dominance over his world which leads to the fear of emasculation, the sense of nostalgia for a lost male company, and the post-traumatic stress disorders caused by his terrible war experience.